SOME STATISTICS METHOD IN TECHNICAL EDUCATION - HREHOVA, Stella (Trends in education, 2009)
In this paper are shown some basic statistic methods which are used such as the tools of statistical process control. There is described a necessity to teach this object in technical education. The aim is to prepare the graduates to solve a task off this area.
Keywords: statistics; quality; manufacturing process.